Construction and application of SDN innovative experimental platform - Yingzheng HAN; Meng WANG; Yiqin LU (Dianxin kexue)
Software-defined networking (SDN) is a new future network architecture,and it has become a hotspot in recent years.SDN experimental platform is an important way for future network architecture teaching and practicing.Some limitations were presented in current SDN experiments which commonly used pure software simulation environment.Based on the real hardware environment and the combination of virtualization and cloud computing technology,an SDN experimental platform for applying innovation was constructed.The availability and effectiveness of the experimental platform were verified by three SDN application innovation competitions.